Verbal Memory Impairments in Children after Cerebellar Tumor Resection - Matthew P. Kirschen; Mathew S. Davis-Ratner; Marnee W. Milner; S. H. Annabel Chen; Pam Schraedley-Desmond; Paul G. Fisher; John E. Desmond (Behavioural Neurology)
This study was designed to investigate cerebellar lobular contributions to specific cognitive deficits observed after cerebellar tumor resection. Verbal working memory (VWM) tasks were administered to children following surgical resection of cerebellar pilocytic astrocytomas and age-matched controls. Anatomical MRI scans were used to quantify the extent of cerebellar lobular damage from each patient's resection. Patients exhibited significantly reduced digit span for auditory but not visual stimuli, relative to controls, and damage to left hemispheral lobule VIII was significantly correlated with this deficit. Patients also showed reduced effects of articulatory suppression and this was correlated with damage to the vermis and hemispheral lobule IV/V bilaterally. Phonological similarity and recency effects did not differ overall between patients and controls, but outlier patients with abnormal phonological similarity effects to either auditory or visual stimuli were found to have damage to hemispheral lobule VIII/VIIB on the left and right, respectively. We postulate that damage to left hemispheral lobule VIII may interfere with encoding of auditory stimuli into the phonological store. These data corroborate neuroimaging studies showing focal cerebellar activation during VWM paradigms, and thereby allow us to predict with greater accuracy which specific neurocognitive processes will be affected by a cerebellar tumor resection.